PENGEMBANGAN MODUL FISIKA BERBASIS METAKOGNISI PADA MATERI POKOK ELASTISITAS DAN GERAK HARMONIK SEDERHANA - Winarti Winarti; Affa Ardhi Saputri (Jurnal Psikologi Integratif, 2013)
Metacognition is one of the factors that inﬂuence academic achievement. This study aims to 1) produce physics-based metacognition module on material elasticity and simple harmonic motion, 2) determine the quality of metacognition-based physics modules in the subject matter of elasticity and simple harmonic motion, and 3) determine students’ response to metacognitionbased physics modules in the subject matter elasticity and simple harmonic motion. This Research is the R & D with model 4-D, which defne, design, develop, and disseminate. Results of this study are: 1) has been generated based physics modules metacognition in the subject matter of elasticity and simple harmonic motion, 2) quality of metacognition-basedphysics modules in the subject matter of elasticity and simple harmonic motion very well. 3) students’ response to metacognition-based module is also very good